The effect of air, SF6 and C3F8 on immortalized human corneal endothelial cells. Issue 4 (6th September 2016) - Hesse, Marina; Kuerten, David; Walter, Peter; Plange, Niklas; Johnen, Sandra; Fuest, Matthias
Abstract: Purpose: While anterior chamber air bubbles aid attachment during posterior lamellar surgery only for few days, these periods can be prolonged with gases in non‐expanding concentrations. To test the effects of different gas compositions on immortalized human corneal endothelial cells (HCEC‐12), we utilized Transwell inserts with semipermeable membranes as an artificial anterior chamber model. Methods: Human corneal endothelial cells (HCEC‐12) were cultured on Transwell inserts for 24 hr, then flipped, burdened and sunk with titanium rings in medium (M1), as well as filled with 2 ml of air (A), 20% sulphur hexafluoride (SF6) (S), or 12% C3F8 (C). After gas exposition for 24, 48 and 120 hr, cells were evaluated by live/dead staining, cell viability assay and Ki67 immunohistochemistry. Results: Proliferation was significantly reduced (Ki67‐positive fraction; M1, 14.8 ± 2.0%; A, 7.9 ± 1.4%; S, 8.1 ± 1.3%; C, 9.9 ± 2.3%; p ‐ values; A, S, C versus M1 < 0.01), the total cell number decreased and the percentage of dead cells increased under gas exposition, independently of the type of gas (120 hr cell count/2.25 cm 2 : M1 = 660.8 ± 57.0 cells; A = 125.5 ± 17.4 cells, S = 123.5 ± 17.0 cells, C = 118.8 ± 16.6 cells; p ‐ value: M versus A/S/C < 0.001; 120 hr dead cells: M = 2.6 ± 1.0%, A = 8.4 ± 2.7%, S = 9.5 ± 3.2%, C = 11.3 ± 3.1%; p ‐ value: M1 versus A/S/C < 0.01). Medium (M1)‐control also proved significantly higher cell viability values in comparison with the gases, which did not differ significantly among them (120 hr luminescence: M1 = 1752.2 ± 91.4, A = 433.0 ± 30.3, S = 507.8 ± 23.3, C = 523.8 ± 20.3; p‐value: M1 versus A/S/C < 0.01). Conclusions: Gas exposition led to a reduction in proliferation and an increase in cell death in HCEC‐12, independently of the gas composition.